Nocturnal Imaginaries: Rethinking and Redesigning the City After Dark - Dunn, Nick (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
How do the multi-sensory experiences and aesthetics of nocturnal places enable us to reimagine how those environments might be? In addition, how do those who inhabit the urban night through their labour engage with its aesthetics and develop knowledge of specific geographies? This paper draws upon ongoing autoethnographic fieldwork including encounters and exchanges with a range of night workers and creative practitioners based in the city of Manchester, UK, to explore the entanglements between light and dark, work and respite, creativity and place. This paper proposes that understanding how nightscapes are used differently by various people is valuable to shaping how they may evolve. This is of critical importance if we are to develop wider and deeper knowledges of the situated, relational, and practised nature of the city after dark, and be able to rethink and reclaim it as a time and place that considers accessibility and equity.